Algorithm for determining the authenticity of biomedical cell preparations containing mesenchymal stem cells - S. S. Druzhinina; M. A. Loginova; D. N. Smirnova; I. P. Obukhov; K. O. Yaroshenko; E. A. Poponina; E. L. Nazarova; N. V. Isaeva; I. V. Paramonov (Сибирский научный медицинский журнал, 2023)
The use of mesenchymal stem cells (MSCs), which have a pronounced immunomodulatory activity, is a promising direction in the development of biomedical cell preparations (BMCPs). In oncohematology, the use of BMCPs containing MSCs is aimed at supporting hematopoiesis during cotransplantation with hematopoietic stem cells (HSCs) and suppressing immune conflicts during allogeneic unrelated transplantation and severe autoimmune processes. An obligatory stage of registration of BMCPs is confirmation of the identity of the MSC cell line (CL), which includes the establishment of morphological characteristics, evaluation of the expression of specific markers and proteins, and confirmation of the genetic stability of CL during cultivation. Determination of markers of genetic stability is possible using various methods, however, according to the recommendations of the American National Standardization Institute, the standard is the analysis of short tandem repeats (STR analysis). The purpose of the study is to develop an algorithm for determining the authenticity of BMCPs containing MSCs, including STR analysis. Material and methods. Identification of MSC cells in BMCP was performed according to the criteria of the International Society for Cell Therapy. Viable cells were counted in a Goryaev chamber. Immunophenotypic characteristics of MSCs were determined by flow cytometry. The level of production of specific proteins was assessed using enzyme immunoassay. Genetic stability markers were identified by STR analysis. Results and discussion. The methods were tested in triplicate for ten BMCP samples to confirm the reproducibility and reliability of the results. The developed algorithm for determining the authenticity of BMCP has a high accuracy, as it includes the STR analysis technique, which makes it possible to identify 19 polymorphic STR markers located on different alleles. Using the method will allow BMCP manufacturers to go through the procedure of state registration of drugs.